What topic modelling can show about the development of agricultural economics: evidence from the Journal Citation Report category top journals. (23rd December 2021) - Cei, Leonardo; Defrancesco, Edi; Stefani, Gianluca
Abstract: Throughout its history, several attempts have been made to map the structure and subfields of agricultural economics; however, these attempts either rely on the experience of distinguished scholars or require processing a massive amount of textual data. This paper investigates the structural dynamics of agricultural economics, focusing on the changing frequency of different subfields and the diversification of the discipline over time and on the differences between European and non-European scholars. A quantitative text analysis is carried out on abstracts from the major agricultural economics journals in the Journal Citation Reports category 'Agricultural Economics and Policy'. The topics identified are consistent with findings from traditional studies, but their importance differs between the two areas. However, a convergence process has been observed in the last years.